Human Right to a Healthy Environment - Knox, John H.; Pejan, Ramin (Cambridge : Cambridge University Press, 2018)
The absence of a globally recognized right to a healthy environment has not prevented the development of human rights norms relating to the environment. Indeed, one of the most noteworthy aspects of human rights law over the last twenty years is that UN treaty bodies, regional tribunals, special rapporteurs, and other human rights mechanisms have applied human rights law to environmental issues even without a stand-alone, justiciable human right to a healthy environment. In The Human Right to a Healthy Environment, a diverse set of scholars and practitioners, all of whom have been instrumental in defining the relationship between human rights and the environment, provide their thoughts on what is, or should be, the role of an international human right to a healthy environment. The right to a healthy environment could be a capstone to this field of law, could help to provide structure to it, or could move it in new directions.
Keywords: Environmental law, International; Human rights -- Environmental aspects; Environmental law, International; Human rights -- Environmental aspects